Effects of irradiation of spray-dried blood meal and animal plasma on nursery pig growth performance - James, B.W.; Webster, M.J.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to determine the effects of irradiation of spray-dried blood meal and animal plasma on nursery pig growth performance. In Exp. 1, irradiation of spray-dried blood meal resulted in improved ADG and F/G and tended to increase ADFI for the 14 d experiment. The majority of the increase in growth performance occurred during the first week of the trial. In Exp. 2, ADG and ADFI were increased from d 0 to 10 for pigs fed irradiated spray-dried animal plasma compared to pigs fed regular spray-dried animal plasma. In addition, we observed differences in growth performance between different sources of spray-dried plasma used in this experiment.
Keywords: Swine; Nursery pig; Irradiation; Blood meal; Animal plasma